2020
DOI: 10.1136/bmjopen-2020-037224
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and understanding the scope and value of the Parkinson’s nurse in the UK (The USP Project): a realist economic evaluation protocol

Abstract: IntroductionThere are multiple configurations of specialist nurses working in the field of Parkinson’s. Parkinson’s Nurse Specialists (PNSs) are recognised as playing a pivotal role; however, there is little published evidence to demonstrate their effectiveness. Further evidence is needed to establish which aspects of the PNSs provide the greatest benefit to people with Parkinson’s and their families, and the cost-effectiveness of different models of care.Methods and analysisRealist approaches explain how and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…( However, conducting this preliminary REE-and especially integrating the economic analyses with our realist analysis, 20 and staying internally coherent with the principles of realist rather than economic evaluation 10 -was challenging. Indeed, as previously mentioned, REE is in its infancy.…”
Section: Methodological Strengths and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…( However, conducting this preliminary REE-and especially integrating the economic analyses with our realist analysis, 20 and staying internally coherent with the principles of realist rather than economic evaluation 10 -was challenging. Indeed, as previously mentioned, REE is in its infancy.…”
Section: Methodological Strengths and Challengesmentioning
confidence: 99%
“…Indeed, as previously mentioned, REE is in its infancy. 10 Although several REE protocols have been published recently in health services research, 20,43,44 there is considerable variation in the extent to which economic analyses are integrated (or not) with realist frameworks. Furthermore, worked examples of REE are extremely rare, 10,19 and to date, are non-existent in the health professions education literature.…”
Section: Methodological Strengths and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PNS role has been developed with the aim of improving PD prognosis, through better education and support, and reducing the impact of PD on patients, but also their families and caregivers. A task force for the PD Society has suggested that each individual with PD will be assigned a healthcare professional, holding a leading role in coordinating the patients’ care and treatment changes in collaboration with a multidisciplinary team ( Brown et al, 2020 ). Today, the PNS role is still recognized as pivotal ( Cook, McNamee, McFetridge, & Deeny, 2007 ) with around 450 PNSs working in primary, secondary, and tertiary care settings in the UK.…”
Section: The Role Of the Parkinson's Disease Nurse Specialistmentioning
confidence: 99%